SPECIES SPECIFICITY OF CHOCOLATE MAHSEER (NEOLISSOCHILUS HEXAGONOLEPIS) AND MALAYSIAN MAHSEER (NEOLISSOCHILUS SOROIDES) - SARMA, DEBAJIT; SANWAL, SUMAN; JHA, GHANSHYAM NATH; MAHANTA, P. C. (Journal of the Inland Fisheries Society of India, 2021)
Ultrastructure of tip of the barbell and arrangement of scales were studied for differentiation of two similar looking Mahseer. The microstructural arrangement of scales of Neolissochilus hexagonolepis, below the focus, was smooth with the presence of spherical structures on the surface. In case of Neolissochilus soroides the micro-structural arrangement was coble shaped. The larval mark between the two species in respect to their size, arrangement, completeness and relative spacing of circuli showed differences. The surface scanning electron micrographs of tip of the barbell of N. hexagonolepis showed thick filamentous structures, while that of N. soroides was compartment like.Key words: Neolissochilus hexagonolepis, N. soroides, ultrastructure, scale, barbel.